Assessing Padlet for Management Information Systems course during Open and Distance Learning / Wan Aryati Wan Ghani, Haslinda Noradzan - Wan Ghani, Wan Aryati; Noradzan, Haslinda (UiTM Press, 2021)
Open and distance learning (ODL) has been used in most higher education institutions in Malaysia and abroad since the Covid-19 outbreak. The learning process must continue, and engaging students is vital in the teaching and learning process. Thus, technologies are on the verge of this situation to substitute traditional face-to-face classes with virtual classrooms. Students and lecturers are the main stakeholders where they need to be mutually connected. For the Management Information Systems course, in particular, the learning environment must be engaging and fun. Therefore, this study proposes Padlet as a learning tool for a comprehensive learning experience that is suitable for both synchronous and asynchronous teaching and learning. This study seeks to examine the usability of Padlet in teaching and learning. It also investigates students' experience when they use Padlet for learning. The nature of Padlet itself offers interesting and fun learning. Based on the survey conducted among students enrolling in this course, Padlet appears to be engaging, interesting, and easy to use as it provides a shorter and quicker way to access learning materials. Its simplicity offers a great way for teachers and students to collaborate.